The Universal Values of Integrity Ūlul Al-Bāb through Work Ethic to Achievement Motivation and Performance of Lecturer at Islamic State University - Irawan, Andik Rony; Mulyadi, Mulyadi; Susilawati, Samsul (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research explores the existential role of Ūlul Al-bāb's universal values in improving work ethic, achievement motivation, and performance at UIN Maulana Malik Ibrahim Malang. Using quantitative methods and Partial Least Square-Sequential Equation Model (PLS-SEM) analysis, this research examines the relationship between variables, emphasizing the mediating role of work ethic. Two hundred respondents were selected from a population of 506 permanent lecturers. The research results show a positive and significant relationship between Ūlul Al-bāb values and both work ethic and performance, which confirms that internalization of objective, moderate, and transcendental principles can improve the performance of lecturers within the institution. However, the direct relationship between Ūlul Al-bāb values and achievement motivation was found to be insignificant. This research also proves that work ethic emerges as an important mediator, linking Ūlul Al-bāb values to both achievement motivation and performance. These findings confirm the importance of translating Ūlul Al-bāb values into performance improvements. The practical implications of these findings are significant for human resource management in higher education.